Transitivity System in Different Spoken Discourses - Sari, Indah; Sembiring, Rosdiana (Journal of Language, Literature and Teaching, 2019)
The aim of this study was to describe the types of processes in transitivity systems used in various spoken discourses and the reasons of using them. This research applied descriptive qualitative design which relies on words to describe the phenomena. The documentation technique was used to achieve the aim of the study. The sources of the data were speech entitled of I Have a Dream by Marthin Luther King published in 1963; the sermon on the mount by Jesus of Nazareth published in 2012; and the song entitled of You Raise Me Up by Josh Groban in 2003. The findings showed that there were six types of processes in speech and sermon but not all types of them were used in the song. The types of processes found in the speech were 139 processes; dominantly was material process which was 60 (43%). There were 76 processes in sermon, and dominantly were 44 (57, 8%) material process; while there were 42 processes in the song; dominantly was 25 (59, 6%) material process. There were 6 reasons of using types of processes in different spoken discourses: 1. physical actions, 2. thinking actions, 3. identifying features, 4. speaking actions, 5. physiological actions and 6. actions that signal the existence of something/someone. It could be concluded that material process are found to be the most dominant in spoken discourse as it represents the process of doing.